An iron-tungsten composite electrode and its use, a heterogeneous electro-Fenton reaction device and a method for treating organic wastewater thereof
By using iron-tungsten composite electrodes in electrofenton technology, using their different hydrophilic properties to achieve efficient treatment of organic wastewater under no aeration conditions, the existing technology has solved the problem of high aeration energy consumption and slow catalytic component circulation speed. , the problem of narrow pH application range has achieved efficient and green sewage treatment.
Patent Information
- Application Number
- CN202310153325.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-23
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-02-23
Smart Images

Figure CN116282390B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of organic wastewater treatment, and in particular to an iron-tungsten composite electrode and application thereof, a heterogeneous electro-Fenton reaction device and a method for treating organic wastewater thereof. Background Art
[0002] Electro-Fenton technology is a combination of electrochemical oxidation technology and chemical Fenton technology. O2 undergoes a 2-electron reduction reaction (2e-ORR) at the cathode to generate H2O2, avoiding the safety hazards caused by the storage and transportation of high-concentration H2O2 solutions. H2O2 further reacts with Fe 2+ The Fenton reaction produces hydroxyl radicals (·OH) to degrade organic pollutants in water, and the Fe 3+ It can gain electrons at the cathode and form Fe 2+ , thereby reducing the amount of catalyst added and the subsequent iron sludge production.
[0003] The synthesis of H2O2 is the key to the Fenton reaction, and most of the electro-Fenton technologies require external aeration devices to provide air or oxygen to provide dissolved oxygen to meet the production of H2O2. Aeration must be maintained throughout the reaction process, which increases the energy consumption and processing cost of the system. Recently, an aeration-free electro-Fenton device has been proposed, which uses super-hydrophobic air diffusion electrodes to capture dissolved oxygen in the solution, but it is not conducive to the circulation of catalytic metal components in the system (Fe 3+ →Fe 2+ ).
[0004] The narrow applicable pH range (2-4) is a key problem that traditional electro-Fenton technology needs to solve. If the pH value of sewage exceeds a certain value, the iron ions dissolved in the solution will flocculate and precipitate, which is easy to produce iron mud. The concentration of iron ions is reduced, which is not conducive to the occurrence of Fenton reaction. In response to this problem, heterogeneous electro-Fenton technology has been gradually developed, mainly focusing on the research of heterogeneous catalysts. Heterogeneous catalysts are dispersed in the solution, which increases the contact area between the active sites and organic pollutants and broadens the applicable pH of the system to a certain extent. However, the dispersed catalysts still have problems such as incomplete separation and recovery and slow circulation of catalytic components. In order to better speed up the circulation of catalytic components and avoid the recovery of catalysts, the catalytic components are fixed on the cathode to prepare a catalytic cathode, and the efficient circulation of catalytic components is achieved under the action of the electric field, thereby improving the stability of the catalyst. At present, most common heterogeneous electro-Fenton devices adopt the method of longitudinally parallel placement of anodes and cathodes, and require external aeration, and the cost of aeration cannot be ignored.
[0005] So far, there are no reports on the removal of refractory organic matter by "floating" heterogeneous electro-Fenton-like catalytic oxidation. Summary of the invention
[0006] In view of the problems existing in the prior art, the present invention provides an iron-tungsten composite electrode, which is prepared by the following method:
[0007] (1) washing and drying the graphite felt and then calcining it in air to obtain hydrophilic graphite felt;
[0008] (2) Glucose, ammonium tungstate and potassium ferrocyanide are dissolved in deionized water in a molar concentration ratio of 1:2:2 to form a mixed solution, the hydrophilic graphite felt obtained in step (1) is placed in the above solution and ultrasonicated for 30 minutes, and then heated at 220° C. for 24 hours; finally, the electrode sheet is taken out and washed and dried to obtain a hydrophilic electrode sheet;
[0009] (3) Ultrasonic vibration is applied to carbon black, polytetrafluoroethylene emulsion and anhydrous ethanol, and the above mixture is coated on one side of the electrode sheet, and then dried and calcined to obtain an electrode with a hydrophobic interface. Through the above steps, an iron-tungsten composite cathode with different hydrophilicity and hydrophobicity on both sides is prepared.
[0010] The iron-tungsten composite electrode can be used as the cathode of a heterogeneous electro-Fenton reaction device. When in use, the iron-tungsten composite electrode floats on the surface of the solution, with the hydrophobic layer side exposed to the air and the hydrophilic layer side downward in contact with the liquid.
[0011] Based on the above technical solution, the present invention also provides a heterogeneous electro-Fenton reaction device, the cathode of which uses the above-mentioned iron-tungsten composite electrode. Specifically, the iron-tungsten composite electrode floats on the surface of the solution, the hydrophobic layer side is exposed to the air, and the hydrophilic layer side is downward in contact with the liquid. A platinum sheet is used as the anode, and the cathode and cathode are arranged in a horizontal and parallel manner.
[0012] The above-mentioned heterogeneous electro-Fenton reaction device is used for organic wastewater treatment, such as removing atrazine from wastewater.
[0013] The present invention has the following advantages:
[0014] (1) The two sides of the iron-tungsten composite cathode have different hydrophilic and hydrophobic properties. The hydrophobic layer is exposed to the air and uses dissolved oxygen from the outside air to synthesize H2O2. The hydrophilic layer carrying the catalytic component is downward in contact with the liquid to catalytically produce active groups. The device does not require external aeration, avoiding the need to recover the catalytic component (Fe 2+ wait).
[0015] (2) Under optimal conditions (near neutrality), the iron-tungsten composite cathode can be reused ten times.
[0016] (3) The introduction of tungsten as a co-catalyst accelerates the reduction of high-valent iron species and promotes the synthesis and transformation of the active group ·OH.
[0017] (4) The heterogeneous electro-Fenton system is applicable to a wide pH range (3.0-11.0). Even under alkaline conditions (pH = 11.0) for 90 min, the initial concentration of 10 mg L -1 A 100% removal rate of atrazine was obtained. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 Schematic diagram of the sewage treatment device of the present invention; 1 is a DC power supply, 2 is an iron-tungsten composite cathode, 3 is a platinum sheet anode, 4 is a magnetic stirring rotor, 5 is a constant temperature magnetic stirrer, and 6 is an iron-tungsten catalytic component side (hydrophilic side);
[0019] Figure 2 The hydroxyl production of the tungsten-iron composite cathode under optimal conditions in Example 1 of the present invention, the hydroxyl production of the composite cathode without adding tungsten-iron in Example 2, and the hydroxyl production of the composite cathode without adding tungsten in Example 3;
[0020] Figure 3 Contact angles on both sides of the composite cathode of Example 1;
[0021] Figure 4 Comparison of atrazine removal rates in Examples 1, 2, and 3;
[0022] Figure 5 Example 4 Atrazine removal rate under different pH conditions;
[0023] Figure 6 Example 5 Repeated stability of the composite cathode;
[0024] Figure 7 The removal rate of the device of the present invention and the conventional reaction device with the anode and cathode placed in parallel in the longitudinal direction (comparative example) when treating atrazine wastewater with a pH value of 5.8 is compared;
[0025] Figure 8 This is a diagram of a conventional reaction device in which the anode and cathode are placed in parallel vertically. DETAILED DESCRIPTION
[0026] The present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be pointed out that the embodiments described below are intended to facilitate the understanding of the present invention and do not have any limiting effect on the present invention.
[0027] Example 1
[0028] This embodiment provides an iron-tungsten composite electrode, which is specifically prepared by the following steps:
[0029] (1) The original graphite felt (2*5 cm) was washed with tap water and ethanol for at least three times, dried, and then calcined in a muffle furnace at 500° C. (with air) for 2 h to obtain hydrophilic graphite felt;
[0030] (2) Glucose, ammonium tungstate and potassium ferrocyanide were dissolved in deionized water in a molar concentration ratio of 1:2:2 to form a mixed solution, a hydrophilic graphite felt was placed in the solution and ultrasonicated at 80 kHz for 30 min, and then transferred to a stainless steel autoclave and heated at 220° C. for 24 hours, then the electrode sheet was taken out and washed with deionized water and anhydrous ethanol, and vacuum dried to obtain a hydrophilic electrode sheet;
[0031] (3) Carbon black (CB) and 60 wt% polytetrafluoroethylene (PTFE) emulsion were mixed in a mass ratio of 1:4, and anhydrous ethanol was added for ultrasonic vibration to form a viscous mixture (the mass ratio of carbon black, polytetrafluoroethylene emulsion and anhydrous ethanol was 1:4:24, wherein the polytetrafluoroethylene emulsion was a concentrated polytetrafluoroethylene dispersion purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., CAS No.: 9002-84-0), and the above mixture was coated on one side of the electrode sheet. After drying, it was calcined in a muffle furnace (calcined at 350°C for 1h) to obtain an electrode with a hydrophobic interface. Through the above steps, an iron-tungsten composite cathode with different hydrophilicity on both sides was prepared.
[0032] like Figure 1 As shown in the figure, the electrode prepared above was used as the cathode, and a platinum sheet (2*5 cm) was used as the anode. The cathode and cathode were placed horizontally and parallel to each other. The composite cathode floated on the surface of the solution, with the hydrophobic layer side exposed to the air and the hydrophilic layer side facing downward in contact with the liquid. 0.05 M sodium sulfate was used as the electrolyte, and the current density was 5 mA cm -2 Without adding pollutants, after 60 min of reaction, the ·OH production reached 97.2 μM ( Figure 2 Curve a);
[0033] The initial concentration was 10 mg L -1 Atrazine was used as the target pollutant, the solution pH was near neutral (pH ≈ 5.8, unadjusted), and the current density was 5 mA cm -2 After 60 min of reaction, the removal rate of atrazine was 100.0% ( Figure 4 Curve a). The contact angles on both sides of the iron-tungsten composite cathode are as follows Figure 3 As shown, the contact angle of the composite cathode side exposed to the air is 149°, which is hydrophobic ( Figure 3 a); The contact angle of the composite cathode on the side in contact with the liquid surface is 0, which is hydrophilic ( Figure 3 b), indicating that the two sides of the composite cathode have different hydrophilicity and hydrophobicity. The hydrophobic layer is exposed to the air and uses the dissolved oxygen in the air to synthesize H2O2. The hydrophilic layer is loaded with metal catalytic components and contacts the liquid surface, which catalyzes H2O2 to generate active groups such as ·OH.
[0034] Example 2
[0035] The difference between Example 2 and Example 1 is that in step (2), the electrode sheet is not modified with the iron-tungsten catalytic component, and the other steps are exactly the same.
[0036] The prepared electrode was used as the cathode, and a platinum sheet (2*5 cm) was used as the anode. The cathode and cathode were placed horizontally and parallel to each other. The composite cathode floated on the surface of the solution, with the hydrophobic layer side exposed to the air and the hydrophilic layer side facing downward in contact with the liquid. 0.05 M sodium sulfate was used as the electrolyte, and the current density was 5 mA cm -2 Without adding pollutants, after 60 min of reaction, the ·OH production was only 9.7 μM ( Figure 2 Curve b);
[0037] The initial concentration was 10 mg L -1 Atrazine was used as the target pollutant, the solution pH was near neutral (pH ≈ 5.8, unadjusted), and the current density was 5 mA cm -2 After 60 min of reaction, the removal rate of atrazine was 43.6% ( Figure 4 Curve b). The iron-tungsten composite cathode proposed by the present invention has a higher catalytic activity than the composite cathode without adding catalytic components.
[0038] Example 3
[0039] The difference between Example 3 and Example 1 is step (2), wherein the hydrophilic graphite felt is placed in a potassium ferrocyanide solution and ultrasonicated for 30 minutes, and transferred to a stainless steel autoclave and heated at 220°C for 24 hours. Subsequently, the electrode sheet is taken out and washed with deionized water and anhydrous ethanol, and vacuum dried to obtain a hydrophilic electrode sheet. The other steps are exactly the same.
[0040] The prepared electrode was used as the cathode, and a platinum sheet (2*5 cm) was used as the anode. The cathode and cathode were placed horizontally and parallel to each other. The composite cathode floated on the surface of the solution, with the hydrophobic layer side exposed to the air and the hydrophilic layer side facing downward in contact with the liquid. 0.05 M sodium sulfate was used as the electrolyte, and the current density was 5 mA cm -2 Without adding pollutants, after 60 min of reaction, the ·OH production was only 69.3 μM ( Figure 2 Curve c);
[0041] The initial concentration was 10 mg L -1 Atrazine was used as the target pollutant, the solution pH was near neutral (pH ≈ 5.8, unadjusted), and the current density was 5 mA cm -2 When the reaction time was 60 min, atrazine ( Figure 4Curve c) has a removal rate of 85.7%. The iron-tungsten composite cathode proposed by the present invention has higher catalytic activity than the composite cathode with only iron added. Tungsten, as a co-catalyst, is conducive to the reduction of high-valent iron species, promotes the conversion of ·OH, and accelerates the removal of pollutants.
[0042] Example 4
[0043] The preparation steps of Example 4 are exactly the same as those of Example 1.
[0044] The prepared electrode was used as the cathode, and a platinum sheet (2*5 cm) was used as the anode. The cathode and cathode were placed horizontally and parallel to each other. The composite cathode floated on the surface of the solution, with the hydrophobic layer side exposed to the air and the hydrophilic layer side facing downward in contact with the liquid. 0.05 M sodium sulfate was used as the electrolyte, and the current density was 5 mA cm -2 , with an initial concentration of 10 mg L -1 Atrazine was used as the target pollutant, and the solution pH was adjusted to 3.0, unadjusted (pH about 5.8), 9.0, and 11.0. When the initial pH of the solution was 3.0, the reaction time was 40 minutes, and the atrazine removal rate was 100.0% ( Figure 5 Curve a); the initial pH value of the solution was not adjusted (pH about 5.8), and the atrazine removal rate was 100.0% after 60 min of reaction ( Figure 5 Curve b); When the initial pH value of the solution was 9.0, the removal rate of atrazine was 100.0% after 75 min of reaction ( Figure 5 Curve c); when the initial pH value of the solution was 11, the removal rate of atrazine was 100.0% after 90 minutes of reaction ( Figure 5 Curve d). The sewage treatment method proposed in the present invention has a good treatment effect on the difficult-to-degrade organic pollutants with a pH value of 3 to 11.0.
[0045] Example 5
[0046] The preparation steps of Example 5 are exactly the same as those of Example 1.
[0047] The prepared electrode was used as the cathode, and a platinum sheet (2*5 cm) was used as the anode. The cathode and cathode were placed horizontally and parallel to each other. The composite cathode floated on the surface of the solution, with the hydrophobic layer side exposed to the air and the hydrophilic layer side facing downward in contact with the liquid. 0.05 M sodium sulfate was used as the electrolyte, and the current density was 5 mA cm -2 , with an initial concentration of 10 mg L -1 The atrazine was used as the target pollutant, and the solution pH was near neutral (pH ≈ 5.8, unadjusted). The repeated stability of the composite cathode was investigated. The results showed that after being reused ten times, the composite cathode still had good catalytic performance. In the tenth cycle, after 60 minutes of reaction, the removal rate of atrazine was about 91.1% ( Figure 6 ). The sewage treatment device proposed by the present invention can effectively slow down the failure of the composite cathode, prolong the service life, and the repeated stability is higher than that of the conventional electro-Fenton system and the traditional electro-Fenton system.
[0048] Comparative Example
[0049] The preparation steps of the comparative example are exactly the same as those of Example 1. The difference lies in the placement of the anode and cathode.
[0050] like Figure 8 As shown, the electrode prepared above was used as the cathode, a platinum sheet (2*5 cm) was used as the anode, the cathode and cathode were immersed in the solution and placed in parallel vertically (without aeration), 0.05 M sodium sulfate was used as the electrolyte, and the current density was 5 mA cm -2 , with an initial concentration of 10 mg L -1 Atrazine was used as the target pollutant, the solution pH was close to neutral (pH ≈ 5.8, unadjusted), and the atrazine removal rate was 80.6% after 60 min of reaction. Figure 7 Curve a); while the anode and cathode are placed horizontally and parallel to each other and the composite cathode floats on the surface of the solution in a "floating" electro-Fenton system (such as Figure 1 When the reaction time was 60 min, the removal rate of atrazine was 100% ( Figure 7 Curve b). The reaction device of the present invention ("floating") is more efficient in removing organic pollutants than the conventional reaction device in which the cathode and anode are placed in parallel longitudinally. The sewage treatment device proposed by the present invention can make full use of the dissolved oxygen in the atmosphere to generate sufficient active oxygen groups, thereby accelerating the removal of pollutants.
[0051] In summary, the present invention uses the prepared iron-tungsten composite electrode with different hydrophilicity and hydrophobicity as the cathode, and proposes a "floating" electro-Fenton-like sewage treatment device and method, which can play the function of integrating efficient synthesis of H2O2 and catalytic oxidation under aeration conditions. The introduction of tungsten accelerates the reduction of high-valent iron, strengthens the production of ·OH, and speeds up the removal of pollutants. It can solve the problems of severe aeration energy consumption, low ·OH yield, slow reduction rate of catalytic components, and narrow pH application range in the current electro-Fenton technology, and achieve the goal of efficient and green sewage treatment.
[0052] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. The purpose of the iron-tungsten composite electrode is characterized by: Cathode for heterogeneous electro-Fenton reaction device; The iron-tungsten composite electrode is prepared by the following method: (1) washing and drying the graphite felt and then calcining it in air to obtain hydrophilic graphite felt; (2) Glucose, ammonium tungstate and potassium ferrocyanide are dissolved in deionized water in a molar concentration ratio of 1:2:2 to form a mixed solution, the hydrophilic graphite felt obtained in step (1) is placed in the above solution and ultrasonicated for 30 minutes, and then heated at 220° C. for 24 hours; finally, the electrode sheet is taken out and washed and dried to obtain a hydrophilic electrode sheet; (3) ultrasonically vibrating carbon black, polytetrafluoroethylene emulsion, and anhydrous ethanol, coating the above mixture on one side of the electrode sheet, drying and calcining to obtain an electrode with a hydrophobic interface. Through the above steps, an iron-tungsten composite cathode with different hydrophilicity and hydrophobicity on both sides is prepared; When in use, the iron-tungsten composite electrode floats on the surface of the wastewater, with the hydrophobic layer side exposed to the air and the hydrophilic layer side facing downward in contact with the wastewater.
2. The use of the iron-tungsten composite electrode according to claim 1, characterized in that: When in use, the platinum sheet is used as the anode, and the cathode and cathode are arranged in a horizontal and parallel manner.
3. A heterogeneous electro-Fenton reaction device, characterized in that: The cathode uses an iron-tungsten composite electrode; The iron-tungsten composite electrode is prepared by the following method: (1) washing and drying the graphite felt and then calcining it in air to obtain hydrophilic graphite felt; (2) Glucose, ammonium tungstate and potassium ferrocyanide are dissolved in deionized water in a molar concentration ratio of 1:2:2 to form a mixed solution, the hydrophilic graphite felt obtained in step (1) is placed in the above solution and ultrasonicated for 30 minutes, and then heated at 220° C. for 24 hours; finally, the electrode sheet is taken out and washed and dried to obtain a hydrophilic electrode sheet; (3) Ultrasonic vibration is applied to carbon black, polytetrafluoroethylene emulsion and anhydrous ethanol, and the above mixture is coated on one side of the electrode sheet, and then dried and calcined to obtain an electrode with a hydrophobic interface. Through the above steps, an iron-tungsten composite cathode with different hydrophilicity and hydrophobicity on both sides is prepared.
4. A heterogeneous electro-Fenton-like reaction device according to claim 3, characterized in that: The iron-tungsten composite electrode floats on the surface of the wastewater, with the hydrophobic layer side exposed to the air and the hydrophilic layer side facing downward in contact with the wastewater.
5. A heterogeneous electro-Fenton-like reaction device according to claim 3, characterized in that: The platinum sheet is used as the anode, and the cathode and cathode are arranged horizontally and in parallel.
6. Use of the heterogeneous electro-Fenton reaction device according to any one of claims 3 to 5, characterized in that: Used for organic wastewater treatment.
7. A method for treating organic wastewater, characterized in that: Use the electro-Fenton reaction device described in any one of claims 3 to 5.
8. The method for treating organic wastewater according to claim 7, characterized in that: During treatment, the current density was 5 mA cm -2 .
Citation Information
Patent Citations
Modified gas diffusion electrode and preparation method thereof
CN108358282A
Horizontal tri-electrode single flow zinc-air battery with a floating cathode
US20190051908A1